2018
DOI: 10.18632/oncotarget.26284
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-198 and -206 during primary tumor progression enables metastatic dissemination in human osteosarcoma

Abstract: The metastatic dissemination is a complex multistep process by which tumor cells from a primary site enter into the systemic circulation to finally spread at distant sites. Even if this mechanism is rare at the tumor level, it remains the major cause of Osteosarcoma-patients’ relapse and mortality. MicroRNAs (miRNAs) have recently been described as novel epigenetics’ genes’ expression regulators actively implicated in cancer progression and dissemination. The understanding of their implication in the metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(43 reference statements)
0
8
1
Order By: Relevance
“…miRNAs and their target genes represent potential novel therapeutic biomarkers for OS (33,34). Previous studies have reported downregulated miR-206 expression in OS cells (35)(36)(37)(38). However, miR-206 expression was demonstrated to be upregulated in human OS tissues in the present study.…”
Section: Discussioncontrasting
confidence: 58%
“…miRNAs and their target genes represent potential novel therapeutic biomarkers for OS (33,34). Previous studies have reported downregulated miR-206 expression in OS cells (35)(36)(37)(38). However, miR-206 expression was demonstrated to be upregulated in human OS tissues in the present study.…”
Section: Discussioncontrasting
confidence: 58%
“…Besides, miR-1301 was reported to be an inhibitor of tumorigenesis in hepatocellular carcinoma cells [28]. In addition, there were some reports indicated that miRNAs could regulate the progression and developments of osteosarcoma (OS) [23, 29, 30]. In the previous report, we found that miR-328-3p was significantly decreased in the hepatocellular carcinoma (HCC) tissues, which was validated by gene microarray analysis [31].…”
Section: Discussionmentioning
confidence: 68%
“…MiRNAs are a type of evolutionarily conserved noncoding RNAs which are about 18–25 nt in length and negatively regulate the gene expression at the posttranscriptional level by directly inhibiting the target genes [22, 23]. The biological function and mechanism of miRNAs have been studied broadly.…”
Section: Discussionmentioning
confidence: 99%
“… 3 It is reported that the 5-year survival rate of patients with osteosarcoma is about 70%. 4 Although our understanding of osteosarcoma has been improved with the deepening of research, there are still many patients with chemotherapy resistance and lung metastasis with a 5-year survival rate of less than 20% and an unfavorable prognosis. 5 , 6 And the molecular mechanisms underlying the development of carcinogenesis and metastasis are still unknown.…”
Section: Introductionmentioning
confidence: 99%